2020
DOI: 10.1590/1807-1929/agriambi.v24n1p52-58
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and evaluation of the DSSAT/Canegro model for sugarcane cultivars under irrigation managements

Abstract: Model calibration is a fundamental factor to obtain high accuracy in the estimation of crop growth and yield. This study aimed to parameterize the genetic and ecotype coefficients of the DSSAT/Canegro model for five sugarcane cultivars kept under three water managements, besides evaluating the accuracy of the model in predicting sugarcane stalk yield, sugar yield and height. Experimental field data were obtained from two years (2016 and 2017) of cultivation at FCAV/Universidade Estadual Paulista, Jaboticabal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
3
1
1
Order By: Relevance
“…Jones et al (2019) found evidence for small but significant G differences in RUEmax. G-specific values for RUEo model trait parameters have been reported by Marin et al (2011b), Dias and Sentelhas (2017) and Coelho et al (2020); GxE rankings in RUEa were not revealed in these results, however. In contrast, RUEo parameter values were not changed during model calibration by Marin et al (2015) and Dias et al (2019).…”
Section: Radiation Use Efficiency (Ruea)contrasting
confidence: 59%
“…Jones et al (2019) found evidence for small but significant G differences in RUEmax. G-specific values for RUEo model trait parameters have been reported by Marin et al (2011b), Dias and Sentelhas (2017) and Coelho et al (2020); GxE rankings in RUEa were not revealed in these results, however. In contrast, RUEo parameter values were not changed during model calibration by Marin et al (2015) and Dias et al (2019).…”
Section: Radiation Use Efficiency (Ruea)contrasting
confidence: 59%
“…Coelho et al. (2020) reported APFMAX values ranging from 0.68 to 0.72 for sugarcane varieties. A prominent characteristic that differentiates energy cane from sugarcane is that energy cane allocates a significant portion of photosynthates to underground rhizomes compared with sugarcane (Matsuoka et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, a sensitivity analysis for the parametrization of cultivar coefficients resulted in an APFMAX value of 0.60, which is the maximum fraction of dry mass increments that can be allocated to aerial dry mass. Coelho et al (2020) reported APFMAX values ranging from 0.68 to 0.72 for sugarcane varieties. A prominent characteristic that differentiates energy cane from sugarcane is that energy cane allocates a significant portion of photosynthates to underground rhizomes compared with sugarcane (Matsuoka et al, 2014).…”
Section: Cultivar Coefficients and Model Performance Evaluationmentioning
confidence: 99%
“…He et al, (2017b) found that data from different weather and site conditions are required to obtain a good calibrated parameter set for a particular cultivar. Improved crop model performance has been reported upon the inclusion of environment-specific parameters in calibration (Coelho et al, 2020). Cultivar-or genotype-and environment-specific parameters already exist in some models (Jones et al, 2003;Wang et al, 2019).…”
Section: Prediction Qualitymentioning
confidence: 99%